Pengaruh Aromaterapi Lemon (Citrus) Terhadap Kualitas Tidur Mahasiswa Tingkat Akhir Sarjana Keperawatan Di Masa Pandemi Covid-19 Tahun 2022 - Zinta Ayu Suryana; Nimsi Melati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
The learning process during the COVID-19 pandemic is done online. Students have obstacles that are often faced when learning online, such as an unstable internet network. This is quite stressful, especially for final year students. High stress can affect sleep quality and adversely affect health. One natural way to treat sleep disorder is lemon aromatherapy. This study aims to determine the effect of lemon (citrus) aromatherapy on sleep quality of final year Bachelor of Science in Nursing. This was quantitative pre-experimental approach with One Group Pretest-Posttest design. The population was 86 final year Bachelor of Science in Nursing students. Non-probability sampling technique was employed with purposive sampling method. The sample was 30 students from 2018 class with sleep quality disorder. The result showed sleep quality before given lemon aromatherapy, 30 respondents (100%) had poor sleep quality, and after given lemon aromatherapy 26 respondents (86,7%) had improved sleep quality, 4 respondents (13,3%) had poor sleep quality. The Wilcoxon Signed Rank Test showed p value of 0.000<0.01. There is an effect of lemon (citrus) aromatherapy on sleep quality of final year Bachelor of Science in Nursing students.